SUMBER DAN APLIKASI MODAL KERJA (SEBUAH ANALISIS PADA PT ALHAMDULILLAH BERKAH BAROKAH) (Manajemen & Bisnis Jurnal, 2022)
PT Alhamdulillah Berkah Barokah is a distributor of LPG gas that was established with a background of social concern for the community and also for children who want to receive free education through a family-owned foundation. Determining the right source and use of working capital is necessary in order to achieve company success in the short or long term. Working capital is defined as the capital used to finance the company's daily operations, especially those with a short term. The focus of this research is to find out how PT Alhamdulillah Berkah Barokah obtains and uses its working capital. Working capital at PT Alhamdulillah Berkah Barokah has the overall meaning of the funds and also the intention at the beginning that was used to set up to meet the operational needs of the company. Sources of working capital are obtained from internal companies and are used for business operational purposes. The components of working capital consist of cash, accounts receivable, and income. This research combines a case study approach with a descriptive qualitative methodology. The results of the study show that the management of sources and use of PT Alhamdulilah Berkah Barokah's working capital is not affected by the presence of covid-19 in 2020 to 2021. PT Alhamdulillah Berkah Barokah can still successfully carry out its business operations and consistently obtain profits that are used as additional working capital and also used for social activities during the Covid-19 pandemic